ASPECTOS DE LA BIOLOGIA EVOLUTIVA DE ESPECIES DE TEPHRITIDAE (DIPTERA) DE DISTRIBUCION CHILENA - Frías L., D. (Acta Entomológica Chilena, 2022)
There are about 4.000 described species of Thephritidae (Díptera). The origin of this family is unknown, ñor are the phylogenetic relations among the species and the mechanisms which generate and maintain the genetic variation in natural populations well understood. Sludies in evolutionary biology have shown that different subfamilies may be separated and characterized according to their hosts, genetic distance and chromosomal mechanisms of sex determination. For some chilean species their phylogenetic relationships has been established through the electrophoretic method. This analysis indicates a corelalion between the genetic identity of these flies and the taxonomic similarity of their plant hosts, which suggests a parallel evolution between insects and plants. This paper presents a list of species, genera and subfamilies of Tephritidae in Chile for which plants are known. These hosts also are Usted. Also the citotaxonomy of the Thephritidae is review, with emphasis on the neotropical and specially the chilean species which I have previously studied, to establish the similarities and differences among species of various subfamilies. In Chile the subfamily Tephritinae is the one with the most genera and species, which always are associaled with plants of the family Compositae. Regarding the chromosomal mechanisms of sex determination this group is characterized by a ZW chromosomic system, or the sex chromosomes apparently are isomorphic. On the other hand, the subfamily Trypetinae offers a reduced taxonomic diversity, infesting groups of plants of other families. Flies in this subfamily have a XY mechanism of sex determination, which corresponds to the oldest chromosomic sex determination system in the díptera.